Emergent behaviour from collective systems underpins the success of 'smart networks'.
'Smart networks' depend on an understanding of both the workings of individual components, as well as interactions across the system. The EU-funded QUANTICOL project has contributed by developing a descriptive language for these systems, building on recent breakthroughs in the field of Formal Methods.